2009
DOI: 10.1016/s0377-1237(09)80008-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Posterior Capsular Opacification following Phacoemulsification, Extracapsular and Small Incision Cataract Surgery

Abstract: Posterior capsular opacification following cataract surgery can be minimized by the use of small incision cataract surgery and phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…Similar results were reported by Moulick et al20 in India (standard or conventional ECCE = 28.1%, MSICS = 15.4%, P = 0.69) and Guzek and Ching14 in Ghana (MSICS = 21.9%, conventional ECC = 12.5%; P = 0.127). Surgical technique is therefore not a risk factor for the development of secondary cataract.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported by Moulick et al20 in India (standard or conventional ECCE = 28.1%, MSICS = 15.4%, P = 0.69) and Guzek and Ching14 in Ghana (MSICS = 21.9%, conventional ECC = 12.5%; P = 0.127). Surgical technique is therefore not a risk factor for the development of secondary cataract.…”
Section: Discussionsupporting
confidence: 88%
“…Our value is higher than the 4.7% reported by Muhammad et al18 in Pakistan. Factors such as age, etiology of cataract, type of surgery, and duration of postoperative follow-up could account for these differences 19,20…”
Section: Discussionmentioning
confidence: 99%
“…Those procedures' factors could be minimized by doing phacoemulsification. 5,16 In this study, the cross tabulation evaluated IOL factors in phacoemulsification group only. It was considered to minimize bias due to surgical technique difference.…”
Section: Discussionmentioning
confidence: 99%
“…The above study findings are consistent with the reported PCO cases in Moulick et al study among 150 patients. 11 In a comparative study by Moin et al, between Hydrophobic Acrylic and polymethyl methacrylate (PMMA) intraocular lenses on incidence of PCO after cataract surgery found that PCO development was 6.2% with hydrophobic Acrylic IOLs and it was 23.4% with PMMA lenses. 12 In the present study among the 184 participants, 13% had history of implantation of Acrylic IOL during cataract surgery which less than the PMMA IOL implantation (87%).…”
Section: Discussionmentioning
confidence: 99%